Militantisme pédagogique, essor du cinéma non commercial et transactions intellectuelles (UFOCEL 1945-1950) - Philippe Bourdier (Mise au Point)
Philippe Bourdier's article considers the actions and doctrine of the Union Française des Offices du Cinéma Educateur Laïque, as they were outlined between 1945 and 1950. How did UFOCEL participate in the intellectual transactions that allowed the development of a scholarly discourse during this period? How did the desire to help teachers who became projectionists out of militancy contribute to the development of an original approach that reconciled the technological knowledge of projection devices and the popularization of the theories of cinema at the time?